MEDICAL COMORBIDITIES AMONG PERSONS WITH DEMENTIA: LINKS TO CAREGIVERS' EMOTIONAL CAREGIVING DIFFICULTIES. (11th November 2018) - Polenick, C A; Min, L; Kales, H C
Abstract: Comorbid health conditions complicate the care of persons living with dementia (PWDs), yet little is known about their impact on family caregivers. We examined how medical comorbidities among PWDs are associated with emotional caregiving difficulties. The U.S. sample included 351 co-resident caregivers from the 2011 National Health and Aging Trends Study and National Study of Caregiving. Multiple linear regressions were estimated to determine links between PWDs' diagnosis of eight chronic health conditions (arthritis, cancer, diabetes, heart disease, hypertension, lung disease, osteoporosis, and stroke) and caregivers' emotional caregiving difficulties. PWDs' diagnosis of diabetes and osteoporosis were independently linked to greater emotional caregiving difficulties, controlling for caregivers' sociodemographic characteristics, care tasks, positive and negative perceptions of caregiving, negative caregiving relationship quality, PWDs' physical impairments, and both care partners' number of chronic conditions. Routine clinical care and interventions to sustain each care partner's well-being should support caregivers in managing medical comorbidities of dementia.